‘Is voice inevitable in written texts?’ Animate agents followed by active verbs as writers’ (de)voicing mechanisms in knowledge dissemination practices - Herrando-Rodrigo, Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2022)
Writers’ identity (Ivanič, 1998) and positioning in written text have been studied under multiple terms. However, a clearer distinction should be made between writers’ positioning (Hyland, 2005a) and writers’ presence or voice (John, 2005). This paper explores how disseminators and specialised writers adapt or mediate the voice of the researchers and writers of medical research articles (Med-RAs) in the corresponding medical popularizations published on-line (Med-E-Pops). By manually scanning a self-compiled corpus of 40 Med-RAs and their 40 Med-E-Pops published in digital sources, it will be shown how evidence of the most personal authorial voice used in research articles, self-mentions, are adapted in the Med-E-Pops texts using other (de)voicing mechanisms. Results from the data-driven analysis show that whereas Med-RAs researchers claim their authorship, knowledge and prestige, Med-E-Pops writers make their own voice negligible to guide the readers’ attention back to the Med-RAs writers’ presence. Med-E-Pops writers ratify Med-RAs writers’ agency creating trustworthy texts for the audience.